The resistance of routing protocols against DDOS attack in MANET - Maha Abdelhaq; Raed Alsaqour; Mada Alaskar; Fayza Alotaibi; Rawan Almutlaq; Bushra Alghamdi; Bayan Alhammad; Malak Sehaibani; Donia Moyna (Institute of Advanced Engineering and Science, 2020)
A Mobil Ad hoc Network (MANET) is a wireless multi-hop network with various mobile, self-organized and wireless infrastructure nodes. MANET characteristics such as openness restricted resources and decentralization impact node efficiency and made them easy to be affected by various security attacks, especially Distributed Denial of Service (DDoS) attacks. The goal of this research is to implement a simulation model called DDoS Attack Simulation Model (DDoSM) in Network Simulator 2(NS-2) and to examine the effect of DDoS Attack on various routing protocol types in MANET namely: Zone Routing Protocol (ZRP), Ad hoc On-Demand Distance Vector (AODV) protocol and Location-Aided Routing (LAR) protocol. The introduced model uses the NS-2 simulator to apply DDoS on the three chosen routing protocols. In terms of throughput and end-to-end latency under the consequences of the attack, the performance of three routings protocols was analyzed.